Gamma‐band harmonic responses for beta‐band auditory steady‐state response are intact in patients with early stage schizophrenia - Mariko Tada; Kenji Kirihara; Tatsuya Nagai; Shinsuke Koike; Tsuyoshi Araki; Kiyoto Kasai (Wiley, 2024)
Abstract Gamma oscillations, thought to arise from the activity of ɣ‐aminobutyric acid (GABA)ergic interneurons, have potential as a biomarker for schizophrenia. Gamma‐band auditory steady‐state responses (ASSRs) are notably reduced in both chronic and early‐stage schizophrenia patients. Furthermore, alterations in gamma‐band ASSRs have been demonstrated in animal models through translational research. However, the 40‐Hz harmonic responses of the 20‐Hz ASSR are not as well‐characterized, despite the possibility that these harmonic oscillatory responses may reflect resonant activity in neural circuits. In this study, we investigated the 40‐Hz harmonic response to the 20‐Hz ASSR in the early stages of schizophrenia. The study recruited 49 participants, including 15 individuals at ultra‐high‐risk (UHR) for psychosis, 13 patients with first‐episode schizophrenia (FES), and 21 healthy controls (HCs). The 40‐Hz harmonic responses of the 20‐Hz ASSR were evident in all groups. Interestingly, while previous report observed reduced 40‐Hz ASSRs, the 40‐Hz harmonic responses of the 20‐Hz ASSR were not reduced in the UHR or FES groups. These findings suggest that the gamma‐band ASSR and its harmonic responses may represent distinct aspects of pathophysiology in the early stages of schizophrenia.